Prove that 1/2 tan (x/2)+1/4tan(x/4)+...+(1/2n )tan (x/2n )=(1/2n )cot(x/2 n ) - cotx for all n (- N and 0<x<(pi/2).

Please recheck your question and get back to us.

  • -12

d

  • -16

Prove that1/2tan (x/2)+1/4tan(x/4)+...+(1/2n)tan (x/2n)=(1/2n)cot(x/2n) - cotx for all n (- N and 0

Asked byaruch
  • -13

1/2tan (x/2)+1/4tan(x/4)+...+(1/2n)tan (x/2n)=(1/2n)cot(x/2n) - cotx for all n (- N and 0

  • -6

Prove that1/2tan (x/2)+1/4tan(x/4)+...+(1/2n)tan (x/2n)=(1/2n)cot(x/2n) - cotx for all n (- N and 0

  • -8
What are you looking for?